2013
DOI: 10.1186/1476-4598-12-147
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: α-santalol inhibits the angiogenesis and growth of human prostate tumor growth by targeting vascular endothelial growth factor receptor 2-mediated AKT/mTOR/P70S6K signaling pathway

Abstract: BackgroundVEGF receptor 2 (VEGFR2) inhibitors, as efficient antiangiogenesis agents, have been applied in the cancer treatment. However, recently, most of these anticancer drugs have some adverse effects. Discovery of novel VEGFR2 inhibitors as anticancer drug candidates is still needed.MethodsWe used α-santalol and analyzed its inhibitory effects on human umbilical vein endothelial cells (HUVECs) and Prostate tumor cells (PC-3 or LNCaP) in vitro. Tumor xenografts in nude mice were used to examine the in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 40 publications
3
35
0
Order By: Relevance
“…According to several studies, protein kinases, including AKT, mTOR, p70S6K and VEGFR‐2 kinase, can regulate angiogenesis . Here, treatment with Mtp significantly increased the phosphorylation of mTOR, p70S6K and 4EBP1, and significantly decreased the autophagy level with up‐regulated SQSTM1/p62 and down‐regulated Beclin‐1 levels.…”
Section: Discussionmentioning
confidence: 86%
“…According to several studies, protein kinases, including AKT, mTOR, p70S6K and VEGFR‐2 kinase, can regulate angiogenesis . Here, treatment with Mtp significantly increased the phosphorylation of mTOR, p70S6K and 4EBP1, and significantly decreased the autophagy level with up‐regulated SQSTM1/p62 and down‐regulated Beclin‐1 levels.…”
Section: Discussionmentioning
confidence: 86%
“…mTOR is a multi-functional kinase associated with the regulation of important cellular processes (25). Phosphorylation of p70S6K can promote mRNA translation and the cell cycle (26). Restraining mTOR can lead to blocked p70S6K phosphorylation and translation, thereby causing cell cycle arrest and induction of apoptosis (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that activation of Akt and ERK pathways, which can be detected by the phosphorylation of these two proteins, mediates neurogenesis in PC12 cells [17] and in human umbilical vein endothelial cells [18] . Therefore, we investigated the effects of Rd on the phosphorylation of Akt and ERK1/2.…”
Section: Effects Of Rd On Akt and Erk Signaling Activation In Pc12 Cementioning
confidence: 99%